2018
DOI: 10.15517/ijds.v0i0.35324
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Tissue Response of PLA Nanofiber Scaffolds Sterilized by Different Techniques

Abstract: In recent years, tissue engineering has evolved considerably, due to the problems in the biomedical area concerning tissue regeneration therapies. Currently, work has been focused on the synthesis and physicochemical characterization of poly lactic acid scaffolds, a synthetic polyester that has been extensively study for its excellent biocompatibility and biodegradability. Moreover, sterilization strategies of scaffold are a crucial step for its application in tissue regeneration, however, the sterilization pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…As demonstrated by our results, the SEM images of the PLA/ZrO 2 nanocomposite had a random orientation of the fiber morphology with a submicron/nanometer range between 100 nm up to 1 µm in diameter, with an average size of 395 nm; by FTIR, it was possible to detect differences between the intensity peak of 0.5 and 0.1 g of ZrO 2 that could be related to the mass fraction of the nanoceramic for 0.1 g (~0.0099 g) and for 0.5 g (~0.047 g) in the composite. This difference in the peak intensity of samples showed that, with increased concentrations of nanoceramic, the corresponding interaction of the Zr-O bonds with the characteristic bands of the functional groups of PLA (carbonyl group, esters CH and CH 3 ) at 758 cm −1 could be detected; furthermore, this different concentration improves the anisotropic properties of the scaffold that could be related to the adhesion between the interface of the fiber matrix and the nanoceramic particles, in concordance with previous studies reported [ [25][26][27]36,37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As demonstrated by our results, the SEM images of the PLA/ZrO 2 nanocomposite had a random orientation of the fiber morphology with a submicron/nanometer range between 100 nm up to 1 µm in diameter, with an average size of 395 nm; by FTIR, it was possible to detect differences between the intensity peak of 0.5 and 0.1 g of ZrO 2 that could be related to the mass fraction of the nanoceramic for 0.1 g (~0.0099 g) and for 0.5 g (~0.047 g) in the composite. This difference in the peak intensity of samples showed that, with increased concentrations of nanoceramic, the corresponding interaction of the Zr-O bonds with the characteristic bands of the functional groups of PLA (carbonyl group, esters CH and CH 3 ) at 758 cm −1 could be detected; furthermore, this different concentration improves the anisotropic properties of the scaffold that could be related to the adhesion between the interface of the fiber matrix and the nanoceramic particles, in concordance with previous studies reported [ [25][26][27]36,37].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, poly(lactic acid) fiber scaffolds were successfully fabricated, and our in vitro biological response of mesenchymal stem cells showed that the polymer concentration and fiber size influenced the biocompatibility response. Furthermore, our results indicated that nanofibrous topography possesses the potential to enhance cell adhesion and proliferation and improve the cues to guide the fiber orientation by the cells; additionally, our in vivo studies showed that PLA fiber spun scaffolds are not cytotoxic in a Wistar rat model [24][25][26]. Moreover, our previous results, where we reported the synthesis of polymer composites composed of PLA/ZrO 2 to attempt optimization of the fabrication by AJS, showed that composites have a fibrous morphology with a random distribution, with a diameter of fibers and mechanical properties depending on polymer and zirconia concentrations, suggesting that the PLA/ZrO 2 composite may be used as a biomaterial [27].…”
Section: Introductionmentioning
confidence: 65%
“…The total cross-section of the photon interaction with matter (σγ) as a function of the photon's energy in the Hydrogen, Carbon, and Oxygen, derived from the Xcom code [14]. knock-on atoms (PKAs) spectrum and their types in the PCL scaffold were investigated.…”
Section: Figurementioning
confidence: 99%
“…Recently, many experimental studies have been performed to investigate the damage of sterilization by gamma-rays, which can lead to structural modification or loss of properties in polycaprolactone (PCL) scaffolds [1-4, 6, 7]. All of these studies have been the product of experimental results [2,[8][9][10][11][12][13][14][15], and the lack of theoretical damage calculations and simulations is felt in this field. In general, aliphatic polymers, such as PCL, are sensitive to radiation, and gamma radiation may affect their physical properties to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in material *e-mail: marcoalv@unam.mx science manufacturing allow alternatives to address several challenges in the treatment of bone tissue. An example of such advancement is the air-jet spinning (AJS) technique, emerging for its flexible simplicity as highly and low-cost processes able to manipulate materials by utilizing gas pressure forces, giving the unique opportunity to design sheet-like platforms that could mimic the densely packed fibrillary structure of the ECM that address and promote better cell adhesion, cell spreading and cell fate during regeneration processes [9][10][11] . However, despite a fine control of the spinning process by the AJS that could guarantee tunable physicochemical and mechanical properties, polymer spun fibers show several limitations in terms of bioactivity, thus negatively influencing communication mechanisms between cells.…”
Section: Introductionmentioning
confidence: 99%